OVERCONFIDENCE, LOSS AVERSION, DAN DISPOSITION EFFECT DALAM PENGAMBILAN KEPUTUSAN INVESTASI: PERAN MODERASI ROBO ADVISOR - Olivia, Amanda; Afandy, Chairil (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2025)
In the current digital era, the use of robo advisor services is gaining importance as it has the potential to help investors susceptible to behavioral biases make more rational investment decisions. This study aims to investigate the effect of overconfidence, loss aversion, and the disposition effect on investment decisions, as well as to examine the moderating role of robo advisor in the relationship between these biases and investment decisions. This study employs a quantitative approach with a survey design. The research population consisted of investors who used robo advisor services to make investment decisions in the Indonesian capital market, with a total of 197 respondents obtained through convenience sampling. The data were analyzed using PLS-SEM through the SmartPLS software. The findings of this study indicate that overconfidence, loss aversion, and the disposition effect have a positive and significant influence on investment decisions. In addition, this study found that robo advisor significantly moderated the influence of overconfidence and disposition effect on investment decisions. However, moderating role of robo advisor was not supported in the relationship between loss aversion and investment decisions. This study confirms that the influence of behavioral biases on investment decisions and how robo advisor plays a role in managing behavioral biases. The practical implications encourage investors to utilize technology such as robo advisor services to reduce behavioral biases.